"PI3K delta syndrome associated with systemic lupus erythematosus" - Elias A Alraqibah, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Activated PI3K delta syndrome (APDS) is an uncommon primary immunodeficiency that arises from gain-of-function mutations in the PIK3CD gene. Clinical features of APDS include immune dysregulation, which leads to recurrent infections, lymphoproliferation, and autoimmune manifestations. SLE is a chronic autoimmune disease wherein pathogenic autoantibodies are produced and manifest multisystem inflammation. The concomitance of APDS and SLE is rare and presents considerable challenges in diagnosis and treatment because of the contradictory coexistence of immune deficiency and autoimmunity. Case Presentation: The patient was a 6-year-old Saudi girl who presented with recurrent pneumonia, lymphadenopathy, hepatosplenomegaly, and bronchiectasis and had received an initial diagnosis of dysgammaglobulinemia that subsequently progressed towards common variable immunodeficiency. SLE developed features of autoimmune disease over time, including elevated anti-double-stranded DNA, polyarthritis, and, finally, pancytopenia. Mutations in the PIK3CD gene were identified using whole-exome sequencing, where the patient was heterozygous. Clinical outcomes improved due to a multidisciplinary approach that included various medications targeting recurrent infections and autoimmune complications. Conclusion: The clinical dilemmas and therapeutic challenges regarding the coexistence of the two disease entities are brought to light. Their coexistence warrants genetic testing in patients who exhibit overlapping immunodeficiency and features of an autoimmune disease. Early diagnosis combined with a personalized treatment plan is pivotal in optimizing outcomes in cases with such rare and complex pathology.